Modified biphenyl Hsp90 C-terminal inhibitors for the treatment of cancer. Issue 18 (15th September 2017) - Forsberg, Leah K.; Liu, Weiya; Holzbeierlein, Jeffrey; Blagg, Brian S.J.
Graphical abstract: Abstract: Heat Shock Protein 90 (Hsp90) is a molecular chaperone under clinical investigation for the treatment of neurodegenerative diseases and cancer. Neuroprotective Hsp90 C-terminal inhibitors (novologues) contain a biaryl ring system, and include KU-596, which was modified and investigated for potential anti-cancer activity. Incorporation of a benzamide group onto the biaryl novologues in lieu of the acetamide yielded compounds that manifest anti-cancer activity. Further exploration of the central phenyl ring led to compounds with enhanced anti-proliferative activity. The design, synthesis, and evaluation of these new analogs against breast and prostate cancer cell lines is reported herein, where it was found that8b and10 manifest potent anti-proliferative activity and a robust degradation of Hsp90 client-dependent proteins.